1994
DOI: 10.3109/15513819409024273
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Hyperplastic Nephromegaly, Nephroblastomatosis, and Renal Dysplasia in a Newborn: A Variety of Universal Nephroblastomatosis

Abstract: A preterm boy was born at 34 weeks. Prenatal ultrasonography showed oligohydramnios, fetal ascites, large kidneys, and small thorax. He died 21 h after birth of respiratory insufficiency. Autopsy revealed Potter's-like facies, hypoplastic lungs, ascites, and bilateral nephromegaly (renal weight almost 10 times normal). The kidneys were finely nodular externally, solid, and cerebriform on cut section. Histologically, they showed a diffusely distorted architecture of jumbled lobules, hyperplasia of cortical-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The case published in 1994 contained a more classical renal blastemal comprising confluent perilobar nephrogenic rests with an associated renal dysplasia. On the other hand, the 1996 case had tubular differentiation resembling the epithelial component of some Wilms tumors [10,11]. Lastly, a more recent report on two siblings with bilateral nephromegaly and autopsy proven universal NB, suggested an autosomal recessive mode of inheritance [12].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The case published in 1994 contained a more classical renal blastemal comprising confluent perilobar nephrogenic rests with an associated renal dysplasia. On the other hand, the 1996 case had tubular differentiation resembling the epithelial component of some Wilms tumors [10,11]. Lastly, a more recent report on two siblings with bilateral nephromegaly and autopsy proven universal NB, suggested an autosomal recessive mode of inheritance [12].…”
Section: Discussionmentioning
confidence: 94%
“…The autopsy revealed generalized visceromegaly, islet cell hyperplasia and hypertrophy, and nephroblastomatosis. Several small series and single case reports of NB detected at autopsy have followed over the course of the next three decades [8][9][10][11]. A series by De Chadarevian et al described four children with nephromegaly detected on physical examination and confirmed by imaging.…”
Section: Discussionmentioning
confidence: 99%
“…This unique case of N B does not fit neatly into the classification scheme proposed by Beckwith et al [ 11. It comes closest to universal NB, the rarest type, ofwhich only a handful of cases are reported [5,. Beckwith et al…”
Section: Discussionmentioning
confidence: 96%
“…It includes diffuse hyperplastic perilobar NB, previously called superficial diffuse or massive NB [ 3 , 41, and the very rare universal NB [5]. We present a new and apparently unique morphologic variant of pure, clinically striking N B in a neonate.…”
mentioning
confidence: 95%
“…The variant of universal nephroblastomatosis is very uncommon. All reported cases of universal nephroblastomatosis have occurred in infants younger than 4 months old [1][2][3][4][5][6], almost all were bilateral. Most of these cases were associated with other congenital abnormalities.…”
Section: Introductionmentioning
confidence: 99%